High speed digital design : design of high speed interconnects and signaling - Zhang, Hanqiao; Krooswyk, Steven; Ou, Jeffrey (Morgan Kaufmann is an imprint of Elsevier, 2015)
High Speed Digital Design discusses the major factors to consider in designing a high speed digital system and how design concepts affect the functionality of the system as a whole. It will help you understand why signals act so differently on a high speed digital system, identify the various problems that may occur in the design, and research solutions to minimize their impact and address their root causes. The authors offer a strong foundation that will help you get high speed digital system designs right the first time. Taking a systems design approach, High Speed Digital Design offers a.